Autologous bone marrow transplantation in acute leukemia - Spellberg, B; Schiller, G J (Hematology/oncology clinics of North America, 1999)
Autologous bone marrow transplantation can induce long-term LFS in 20% to 40% of patients with relapsed acute leukemia and should be considered as salvage therapy for patients who lack an HLA-matched donor and for patients over 45. Adult ALL patients and children with ALL in extramedullary relapse beyond second CR should receive alloBMT if at all possible. The role of ABMT in acute leukemia patients in first CR remains unclear despite randomized trials (Table 2). Because protocol deviations, early relapse, and inappropriately high treatment-related mortality unequally affected the ABMT cohort, and because recent randomized trials have used old purging methodologies, it is not possible to conclude that ABMT is not beneficial. More recent studies show that most patients are able to proceed with the intended ABMT and that modern purging may be associated with a treatment-related mortality rate of less then 5%. Immunomodulation and graft engineering uniquely suited to autologous progenitor cells indicate that ABMT should continue to be studied in the management of acute leukemia.